Effectiveness of acupuncture for pain relief in shoulder-hand syndrome after stroke: a systematic evaluation and Bayesian network meta-analysis - Huang, Ting; Yao, Hongfang; Huang, Junneng; Wang, Ning; Zhou, Chunjun; Huang, Xuyang; Tan, Xiangyuan; Li, Yanyan; Jie, Yuyu; Wang, Xiang; Yang, Yu; Liang, Yingye; et al. (Frontiers in Neurology, 2023)
Background Shoulder-hand syndrome (SHS) is a common complication after stroke, and SHS-induced pain significantly hampers patients’ overall recovery. As an alternative therapy for pain relief, acupuncture has certain advantages in alleviating pain caused by SHS after stroke. However, choosing the best treatment plan from a variety of acupuncture options is still a serious challenge in clinical practice. Therefore, we conducted this Bayesian network meta-analysis to comprehensively compare the effectiveness of various acupuncture treatment methods. Methods We systematically searched for randomized controlled trials (RCTs) of acupuncture treatment in patients with post-stroke SHS published in PubMed, Embase, Cochrane, and Web of Science until 9 March 2023. We used the Cochrane bias risk assessment tool to assess the bias risk in the included original studies. Results A total of 50 RCTs involving 3,999 subjects were included, comprising 19 types of effective acupuncture interventions. Compared to single rehabilitation training, the top three interventions for VAS improvement were floating needle [VAS = −2.54 (95% CI: −4.37 to −0.69)], rehabilitation + catgut embedding [VAS = −2.51 (95% CI: −4.33 to −0.68)], and other multi-needle acupuncture combinations [VAS = −2.32 (95% CI: −3.68 to −0.94)]. The top three interventions for improving the Fugl–Meyer score were eye acupuncture [Meyer = 15.73 (95% CI: 3.4627.95)], other multi-needle acupuncture combinations [Meyer = 12.22 (95% CI: 5.1919.34)], and traditional western medicine + acupuncture + traditional Chinese medicine [Meyer = 11.96 (95% CI: −0.59 to 24.63)]. Conclusion Multiple acupuncture methods are significantly effective in improving pain and upper limb motor function in post-stroke SHS, with relatively few adverse events; thus, acupuncture can be promoted. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, CRD42023410957.